Effects of hamstring stretching on passive muscle stiffness vary between hip flexion and knee extension maneuvers - Miyamoto, N.; Hirata, K.; Kanehisa, H. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The purpose of this study was to examine whether the effects of hamstring stretching on the passive stiffness of each of the long head of the biceps femoris (BFl), semitendinosus (ST), and semimembranosus (SM) vary between passive knee extension and hip flexion stretching maneuvers. In 12 male subjects, before and after five sets of 90 s static stretching, passive lengthening measurements where knee or hip joint was passively rotated to the maximal range of motion (ROM) were performed. During the passive lengthening, shear modulus of each muscle was measured by ultrasound shear wave elastography. Both stretching maneuvers significantly increased maximal ROM and decreased passive torque at a given joint angle. Passive knee extension stretching maneuver significantly reduced shear modulus at a given knee joint angle in all of BFl, ST, and SM. In contrast, the stretching effect by passive hip flexion maneuver was significant only in ST and SM. The present findings indicate that the effects of hamstring stretching on individual passive muscles` stiffness vary between passive knee extension and hip flexion stretching maneuvers. In terms of reducing the muscle stiffness of BFl, stretching of the hamstring should be performed by passive knee extension rather than hip flexion.